Improved distribution center by discrete event simulation - Jiménez B., Manuel (2014)
In the present investigation a simulation model was elaborated to propose and to evaluate improvements in a center of distribution of foods of human consumption. They took as indicators to evaluate the acting of the system; the level of service that perform the center, the time of answer, so much in the reception as the despatch and the operative costs. With the simulation model they were executed a series of experiments; as the plant layout of the warehouse, modifications in the reception processes and shipping, obtaining this way a configuration that the yield of the system increases in study in approximately 40%.